2008
DOI: 10.1097/qad.0b013e3282f768f8
|View full text |Cite
|
Sign up to set email alerts
|

Rapid scaling-up of antiretroviral therapy in 10 000 adults in Côte d'Ivoire: 2-year outcomes and determinants

Abstract: In this rapidly scaling-up program, survival and immune reconstitution were good; women and patients followed up in centers with longer experience had better outcomes; outcomes were similar in zidovudine/stavudine-based regimens and in efavirenz/nevirapine-based regimens. Decreasing the rate of loss to follow-up should now be the top priority in antiretroviral treatment rollout.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
170
3
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 166 publications
(200 citation statements)
references
References 31 publications
26
170
3
1
Order By: Relevance
“…In Mali, the study rather focused on line-of-treatment changes and reported a second-line incidence of 3.3/100 PY [9]: a low incidence consistent with the one of our study and other data from developing countries [5,10,[16][17][18][19][20]. The mechanisms of "economy of molecules" can be put forward as an explanation but also the routine nonavailability of the viral load.…”
Section: Hiv-1 and Hiv-d Infections (Comparing Hiv-2 Infection)supporting
confidence: 88%
“…In Mali, the study rather focused on line-of-treatment changes and reported a second-line incidence of 3.3/100 PY [9]: a low incidence consistent with the one of our study and other data from developing countries [5,10,[16][17][18][19][20]. The mechanisms of "economy of molecules" can be put forward as an explanation but also the routine nonavailability of the viral load.…”
Section: Hiv-1 and Hiv-d Infections (Comparing Hiv-2 Infection)supporting
confidence: 88%
“…12 Since the introduction of antiretroviral therapy (ART), many studies from resource-limited settings, particularly in Africa, have described the clinical characteristics, clinical response and treatment outcomes of HIV-1-infected patients on ART. [13][14][15][16][17][18][19][20] However, there is a dearth of similar published information for HIV-2 21,22 and dual HIV-1/2, probably because these infections are less prevalent and are concentrated in West Africa. Although individuals infected with HIV-2 and HIV-1/2 are a considerable minority compared with HIV-1, assessing their baseline characteristics and their response to and outcomes on ART remains important.…”
Section: Introductionmentioning
confidence: 99%
“…4 Low body mass index (BMI < 18 kg/m 2 ) has also been associated with early mortality. [6][7][8][9][10][11][12][13] Unfortunately, only 45% of HIVinfected people know their status, which contributes to the still significant proportion (30%) with a CD4 count < 100 cells/μL at presentation despite raising the CD4 threshold for initiating treatment particularly in men. 14,15 Tuberculosis (TB) is a common cause of ART-associated death [16][17][18] among HIV-infected people in SSA, particularly in east and southern Africa.…”
Section: Introductionmentioning
confidence: 99%